2017
DOI: 10.1002/lpor.201700132
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Lattice Kerker Effect in Metasurfaces With Electric and Magnetic Optical Responses

Abstract: Abstract. To achieve efficient light control at subwavelength dimensions, plasmonic and all-dielectric nanoparticles have been utilized both as a single element as well as in the arrays. Here we study 2D periodic nanoparticle arrays (metasurfaces) that support lattice resonances near the Rayleigh anomaly due to the electric dipole (ED) and magnetic dipole (MD) resonant coupling between the nanoparticles. Silicon and core-shell particles are considered. We demonstrate for the first time that, choosing of lattic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
144
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(160 citation statements)
references
References 78 publications
8
144
0
Order By: Relevance
“…In agreement with present calculations, the numerical results of have shown that arrays as small as 7 × 7 silicon particles are enough to shift the ED resonance, overlap it with MD, and achieve resonant directional scattering (Kerker effect) with forward‐to‐backward scattering ratio up to 50.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In agreement with present calculations, the numerical results of have shown that arrays as small as 7 × 7 silicon particles are enough to shift the ED resonance, overlap it with MD, and achieve resonant directional scattering (Kerker effect) with forward‐to‐backward scattering ratio up to 50.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…">In Section 3, we have shown that scattering spectra of 7 × 7 LIPP‐particle array resemble properties of ‘ideal case’ (array with an effectively infinite number of particles). One can see well‐pronounced peaks at the wavelength close to Rayleigh anomaly (lattice resonances) and forward‐to‐backward scattering ratio as high as 4300.In agreement with present calculations, the numerical results of have shown that arrays as small as 7 × 7 silicon particles are enough to shift the ED resonance, overlap it with MD, and achieve resonant directional scattering (Kerker effect) with forward‐to‐backward scattering ratio up to 50. Lattice resonances have also been shown to be excited even when a substantial number of particles are removed, or particles are shuffled in the array.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In particular, one can utilize the generalized Kerker effect in the metasurface composed of dielectric particles to suppress reflection from the high-index substrate, and in this case, the metasurface serves as an antireflective coating [27,28]. One important class of such structures are reflectionless all-dielectric Huygens' metasurfaces operating on spectrally overlapped MD and ED moments oriented perpendicular to each other with equal magnitude [29,30].…”
Section: Introductionmentioning
confidence: 99%